Decreased Volume of the Cerebral Ventricles on CT Images in Gilles de la Tourette’s Syndrome - Lisbeth Regeur; L. Korbo; N. Bang; B. Pakkenberg (Behavioural Neurology)
The aim of the present study was to estimate the volume of the ventricular system comprising lateral plus third ventricles in patients with Gilles de la Tourette's syndrome on computed tomographic (CT) scannings using unbiased stereological principles and to compare that volume with a control group. We found a significantly reduced ventricular volume in 24 patients with Gilles de la Tourette's syndrome (GTS) compared with 28 controls.